Personalized Gene Expression Analyses of SMAD7 and KLF10 In Breast Cancer - Hosseinzadeh,Ali (2016)
Many cancer researchers use gene expression analysis for differentiation between tumor and normal cells for diagnostic, prognostic and therapeutic purposes. Most of studies compare either tumor cell lines by normal cell lines or tumor tissue of affected individuals by normal healthy control tissue. But expression of each special gene is unique in different individuals and also in different tissue of same individual. For this reason, here we compare the gene expression levels of SMAD7 and KLF10 in tumor cells and its adjacent normal tissue of breast cancer patients and compared them. For this purpose, a total of 40 tumor and matched tumor-free margin samples were obtained during surgery. The SMAD7 and KLF10 mRNA expression levels in tumor and marginal samples were examined by real-time quantitative PCR. Results are not concordant with previous studies and comparison of only SMAD7 or KLF10 is not useful for differentiating between tumor and margin cells, but ratio analysis of these two genes, SMAD7/ KLF10, can be indicative than study of one gene alone. We concluded that gene expression analysis of tumor cells with adjacent normal tissue are essential for precise identification and interpretation of cancer alterations and have important implications for the diagnostic and therapeutic management of cancer patients.